Cytotoxic mixed-ligand complexes of Cu(II): A combined experimental and computational study - Alem, Mamaru Bitew; Damena, Tadewos; Desalegn, Tegene; Koobotse, Moses; Eswaramoorthy, Rajalakshmanan; Ngwira, Kennedy J.; Ombito, Japheth O.; Zachariah, Matshediso; Demissie, Taye B. (Frontiers in Chemistry, 2022)
Herein, we report the synthesis of mixed-ligand Cu(II) complexes of metformin and ciprofloxacin drugs together with 1,10-phenanthroline as a co-ligand. The synthesized complexes were characterized using different spectroscopic and spectrometric techniques. In vitro cytotoxic activity against human breast adenocarcinoma cancer cell line (MCF-7) as well as antibacterial activity against two gram-negative and two gram-positive bacterial strains were also investigated. The analyses of the experimental results were supported using quantum chemical calculations and molecular docking studies against estrogen receptor alpha (ERα; PDB: 5GS4). The cytotoxicity of the [Cu(II) (metformin) (1,10-phenanthroline)] complex (1), with IC50 of 4.29 µM, and the [Cu(II) (ciprofloxacin) (1,10-phenanthroline)] complex (2), with IC50 of 7.58 µM, were found to be more effective than the referenced drug, cisplatin which has IC50 of 18.62 µM against MCF-7 cell line. The molecular docking analysis is also in good agreement with the experimental results, with binding affinities of –7.35, –8.76 and –6.32 kcal/mol, respectively, for complexes 1, 2 and cisplatin against ERα. Moreover, complex 2 showed significant antibacterial activity against E. coli (inhibition diameter zone, IDZ, = 17.3 mm), P. aeruginosa (IDZ = 17.08 mm), and S. pyogen (IDZ = 17.33 mm), at 25 μg/ml compared to ciprofloxacin (IDZ = 20.0, 20.3, and 21.3 mm), respectively. Our BOILED-egg model indicated that the synthesized metal complexes have potentially minimal neurotoxicity than that of cisplatin.